Corrosion products characterisation aimed at restoration of Bronze Age metal artefacts from Garda Lake. Issue 1 (1st April 2022) - Labate, M; Sirello, C; Longhi, C; Aceto, M; Operti, L; Agostino, A
Abstract: Conservation is a complex field that needs an exchange of views among different professionals including archaeologists, conservators, restorers and scientists. Diagnostic analyses can give useful information able to lay down the documentation about the artefacts conservation status before and after the restoration; to define the restoration plan and to lead to the most suitable conservation strategies, materials and methods; to evaluate and track the restoration work and to reproduce it in similar contexts. For all of these reasons, a scientific restoration treatments on cultural heritage need materials and alteration products characterisation as a propaedeutic phase. This awareness has guided the study approach of some Bronze Age metal findings from Garda Lake, analysed in order to know the nature of corrosion products in case of upcoming restoration.